Isolation and Characterization of Simian Retrovirus Type D from Macaca fascicularis and M. nemestrina in Indonesia - DIAH ISKANDRIATI; UUS SAEPULOH; SILMI MARIYA; RICHARD F GRANT; DEDY DURYADI SOLIHIN; DONDIN SAJUTHI; JOKO PAMUNGKAS (Microbiology Indonesia, 2010)
Simian type D retroviruses (SRVs) are one of the causative agents of simian acquired immunodeficiency syndrome (AIDS) in Asian macaques. In the past, SRV isolates from macaques had only been identified at the US primate centers, outside the country of origin and after the animals had been introduced into a new environment. In this study, we report the first isolation, cultivation and molecular characterization of the type D simian retrovirus naturally infecting wild caught macaques in their natural habitats in the country of origin, in this case, Indonesia. When peripheral blood mononuclear cells (PBMC) from Macaca fascicularis (Mf) and M. nemestrina (Mn) were co-cultured with Raji human B-cell line, syncytia were observed microscopically and confirmed by immunofluoresence assay using antibody to SRV-2. Immunoblot analysis of purified Mf-ET1006 from cell culture supernatants demonstrated that the viral core and envelope proteins reacted with rabbit anti-SRV. Sequence analysis of Mf isolates in the viral envelope region revealed high homology to SRV-2 (94-96%). On the other hand, the homologies in the envelope region of Mn isolates were less than 80% to SRV-1, SRV-2, SRV-3 and Mf isolates. This study suggests that the isolate from Mn may be different from any other published SRV isolates.